Sex Differences in Mortality Rates and Underlying Conditions for COVID-19 Deaths in England and Wales - Mohamed, Mohamed O. (Mayo Clin Proc, 2020)
OBJECTIVE: To address the issue of limited national data on the prevalence and distribution of underlying conditions among COVID-19 deaths between sexes and across age groups. PATIENTS AND METHODS: All adult (≥18 years) deaths recorded in England and Wales (March 1, 2020, to May 12, 2020) were analyzed retrospectively. We compared the prevalence of underlying health conditions between COVID and non–COVID-related deaths during the COVID-19 pandemic and the age-standardized mortality rate (ASMR) of COVID-19 compared with other primary causes of death, stratified by sex and age group. RESULTS: Of 144,279 adult deaths recorded during the study period, 36,438 (25.3%) were confirmed COVID deaths. Women represented 43.2% (n=15,731) of COVID deaths compared with 51.9% (n=55,980) in non-COVID deaths. Overall, COVID deaths were younger than non-COVID deaths (82 vs 83 years). ASMR of COVID-19 was higher than all other common primary causes of death, across age groups and sexes, except for cancers in women between the ages of 30 and 79 years. A linear relationship was observed between ASMR and age among COVID-19 deaths, with persistently higher rates in men than women across all age groups. The most prevalent reported conditions were hypertension, dementia, chronic lung disease, and diabetes, and these were higher among COVID deaths. Pre-existing ischemic heart disease was similar in COVID (11.4%) and non-COVID (12%) deaths. CONCLUSION: In a nationwide analysis, COVID-19 infection was associated with higher age-standardized mortality than other primary causes of death, except cancer in women of select age groups. COVID-19 mortality was persistently higher in men and increased with advanced age.